Does MaaS address the challenges of multi-modal mothers? User perspectives from Brussels, Belgium. (October 2022) - Cooper, Erin; Vanoutrive, Thomas
Abstract: In recent years, Mobility as a Service (MaaS) has received considerable attention in transportation research and policy. The MaaS discourse emphasizes its user-oriented nature and flexibility, which, at least in theory, fits well with the more complex mobility patterns of mothers. We use five key perspectives to analyze MaaS and compare this to the existing system and needs of multi-modal mothers: technology, transportation, economics, subject and policy. The study focuses on Brussels, Belgium where MaaS is promoted as a flexible, efficient, multi-modal alternative for private automobile users. Nevertheless, the main offers do not seem to be family-oriented, and the multi-modal and digitally literate mothers included in the study did not find shared modes useful, except for shared cars. MaaS does not seem to capture the challenge in Brussels since walking and transit are already dominant modes, and goods and services, as well as jobs and housing, are spread throughout the city. The needs expressed by participants through interviews included better station access and tram access with strollers, and better infrastructure in general. The elements of MaaS that were useful for participants (integrated fare cards, apps with better information about public transportation arrival times, and infrastructure improvements), were already present in Brussels without a change to the core idea of public transportation, marketization of transportation services, or addition of shared services. This leads to the conclusion that with the development of MaaS, it is important to not lose sight of basic transportation needs. This suggests that MaaS proponents need to focus more on how to meet users' needs rather than trying to "reduce resistance" to MaaS. Highlights: MaaS proponents should shift focus from barriers to MaaS uptake to addressing user needs. Being multi-modal and digitally literate does not always make shared modes useful. Family-oriented options are needed for MaaS to reach a larger user base. Users still benefit from integration efforts, with or without full MaaS adoption. Focus on MaaS could distract attention from needed infrastructure improvements.